Simulasi Pencegahan Blackout Akibat Gangguan Hubung Singkat Di Luar Zona Proteksi Diferensial Pada Jaringan Distribusi Closed Loop Penyulang Kompetensi dan Potensial - Eko Nio Rizki (Sekolah Tinggi Teknik PLN, 2021)
One way to improve the reliability of the power distribution system is to design a good protection system, which is selective, sensitive, reliable, fast, and easy. Through the simulation in this study, the protection system that has been installed will be compared, namely a closed-loop system with differential relay protection with a protection system with additional logic at the relay output, focusing on busbar disturbances belonging to customers substations. The result is that the protection system that has been installed has a drawback, namely when there is a disturbance in the busbar of the customer's substation, the two feeder circuit breakers in the loop system will trip with the required clearance time of 765 milliseconds, while after adding logic to the relay output, when it occurs there is only one feeder circuit breaker that trips while another tripped circuit breaker is at the substation with the required clearance time of 524 milliseconds, so there is only one customer who experiences a blackout.